Brown Marmorated Stink Bug, Halyomorpha halys Ståhl (Insecta: Hemiptera: Pentatomidae) - Jamba Gyeltshen; Gary Bernon; Amanda Hodges (EDIS)
The brown marmorated stink bug (BMSB), Halyomorpha halys (Ståhl), is a recently introduced pest to the western hemisphere and was first officially reported from Allentown, Pennsylvania in 2001 (Hoebeke and Carter 2003). This stink bug may become a major agricultural pest in North America, similar to the southern green stink bug, Nezara viridula (L.). Both species are polyphagous pests of various crops, but the exact potential impact of BMSB is currently unknown until it is detected in agricultural areas. However, in eastern Asia where the BMSB is native or indigenous, it is a pest on fruit trees and soybeans. This document is EENY-346, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2005.